Reflections on Macroeconomics - Perry, George L. W. (American Economic Review, 1984)
The turmoil that has characterized macroeconomics for at least a decade originated with the inflation that emerged in the late 1960's and persisted stubbornly throughout the 1970's. The inability of the neoclassical synthesis to model inflation convincingly spawned the new classical models. Because they infer macroeconomic results more directly from principles of maximizing behavior, they appeal to some as more rigorous. Many others reject them as irrelevant because neither the microeconomic behavior that these models postulate nor their macroeconomic implications are realistic. The central postulates are that all agents are price takers and that all markets clear in the sense of Walrasian auction markets. In a dynamic, or multiperiod, context this means markets clear in rationally expected future prices. The most controversial implications are policy ineffectiveness and, in some versions, the proposition that inflation could be eliminated with little cost in real output. As one of those who was unimpressed with these more provocative postulates and implications, I was distressed that anyone took them seriously, and that the profession became so divided over important policy issues. But it is also true that some more interesting ideas, that were originally linked with the auction-market model by Robert Lucas and other authors, might not have been developed without the controversy. One is that the rational expectations methodology should be applied in a thorough way to macroeconomic relations. Another is that private agents' behavior will depend on the rules governing the conduct of policy, or the policy regime. I am optimistic that we are on the verge of generating more light and less heat than we have been recently. The interesting new ideas and methodology that have developed in the course of the past decade's debates will continue to be explored. But inevitably, I believe, these and other ideas will be examined within the framework of an economy that in crucial ways does not operate with auctionlike markets. Both the lack of empirical success with the classical postulates and the intellectual challenge of developing a more general micro foundation to supplant the auction model are pushing in this direction. With this development, the gap between rigor and reality should narrow as researchers differ less about the basic postulates underlying macro models.